Detection of environmental and morphological adaptation despite high landscape genetic connectivity in a pest grasshopper (Phaulacridium vittatum). Issue 14 (11th July 2019) - Yadav, Sonu; Stow, Adam J.; Dudaniec, Rachael Y.
Abstract: Widespread species that exhibit both high gene flow and the capacity to occupy heterogeneous environments make excellent models for examining local selection processes along environmental gradients. Here we evaluate the influence of temperature and landscape variables on genetic connectivity and signatures of local adaptation in Phaulacridium vittatum, a widespread agricultural pest grasshopper, endemic to Australia. With sampling across a 900‐km latitudinal gradient, we genotyped 185 P. vittatum from 19 sites at 11, 408 single nucleotide polymorphisms (SNPs) using ddRAD sequencing. Despite high gene flow across sites (pairwise F ST  = 0.0003–0.08), landscape genetic resistance modelling identified a positive nonlinear effect of mean annual temperature on genetic connectivity. Urban areas and water bodies had a greater influence on genetic distance among sites than pasture, agricultural areas and forest. Together, F ST outlier tests and environmental association analysis (EAA) detected 242 unique SNPs under putative selection, with the highest numbers associated with latitude, mean annual temperature and body size. A combination of landscape genetic connectivity analysis together with EAA identified mean annual temperature as a key driver of both neutral gene flow and environmental selection processes. Gene annotation of putatively adaptive SNPs matched with gene functions for olfaction, metabolic detoxification and ultraviolet light shielding. Our results imply that this widespread agricultural pest has the potential to spread and adapt under shifting temperature regimes and land cover change.